2022
DOI: 10.1177/03009858221122517
|View full text |Cite
|
Sign up to set email alerts
|

Feline pulmonary carcinoma: Gross, histological, metastatic, and immunohistochemical aspects

Abstract: Feline pulmonary carcinoma (FPC) is an uncommon neoplasm with unique morphological features. We describe the gross, histological, metastatic, and immunohistochemical aspects of FPC, based on postmortem examinations from an 11-year retrospective study. Thirty-nine cases were selected. Predispositions were observed in senior ( P < .001) and Persian ( P = .039) cats. There were three gross patterns of the pulmonary tumors: (a) a large nodule and additional smaller nodules, (b) a solitary nodule, and (c) small,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 52 publications
(141 reference statements)
3
18
0
Order By: Relevance
“…Pulmonary AD was the main primary carcinoma diagnosed in this study, followed by adenosquamous carcinoma. These data corroborate previous literature, which reported that AD is the most frequent primary pulmonary neoplasm diagnosed in cattle, 4,31 as well as in companion animals 8,11,15,43 and in humans. 51,52 Unlike what has been reported in dogs and cats, in which papillary AD is the main subtype, 1,8,11,43 solid AD was the most frequent subtype in our work.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Pulmonary AD was the main primary carcinoma diagnosed in this study, followed by adenosquamous carcinoma. These data corroborate previous literature, which reported that AD is the most frequent primary pulmonary neoplasm diagnosed in cattle, 4,31 as well as in companion animals 8,11,15,43 and in humans. 51,52 Unlike what has been reported in dogs and cats, in which papillary AD is the main subtype, 1,8,11,43 solid AD was the most frequent subtype in our work.…”
Section: Discussionsupporting
confidence: 92%
“…17,31 In these cases, metastases frequently occur in regional lymph nodes, liver, and lung. 17 SCCs usually have intense and diffuse immunoreactivity for squamous cell markers, such as p40, CK5, and CK5/6, 43,50 as observed in this study. These immunomarkers have been used in humans 50 and companion animals.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations